Beyond obsolescence: a twenty-first century research agenda for the langues régionales. Issue 2 (July 2019) - Hall, Damien; Kasstan, Jonathan R.; Hornsby, David
Abstract : This Special Issue of the Journal of French Language Studies celebrates a recent surge in enthusiasm for sociolinguistic studies involving the regional languages of France. Taking our cue from the contributions to the volume, which we introduce here, we argue that a changing twenty-first century landscape offers an exciting new agenda for these regional languages (and minority languages more widely), and set out what we see as six key directions for contemporary research.